Communicating the Corporate Social Responsibility Activities of the UK Division of an International Brewing Company through Sustainability Reporting - Olayinka, Ogunrinade (2009)
Sustainability reporting has risen to prominence in recent years, and has been particularly identified as having the potential to make significant positive contributions to organisational reputation. This project aims to answer the question of how Molson Coors Brewing Company (UK) (MCBC) can best develop its own sustainability reporting in order to enhance the company’s standing both within the alcohol industry and the wider society. In pursuing this aim I draw upon a peer group reporting comparison, a programme of interviews with corporate management and focus group exercises conducted with representative employees.